2014
DOI: 10.1007/s00426-014-0551-y
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing distributional properties of interference effects across modalities: chances and challenges

Abstract: In research investigating Stroop or Simon effects, data are typically analyzed at the level of mean response time (RT), with results showing faster responses for compatible than for incompatible trials. However, this analysis provides only limited information as it glosses over the shape of the RT distributions and how they may differ across tasks and experimental conditions. These limitations have encouraged the analysis of RT distributions using delta plots. In the present review, we aim to bring together re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 67 publications
2
23
1
Order By: Relevance
“…We should note that although the auditory target stimuli in Experiment 1 were presented by the left or right speaker, the lateralized sensory activity elicited by the auditory stimuli should have a limited contribution to motor-related LRPs (e.g., Wascher, Schatz, Kuder, & Verleger, 2001; see also Dittrich, Kellen, &Stahl, 2014, andNeumann, van der Heijden, &Allport, 1986, for further discussion). For instance, Wascher et al (2001, Experiment 2) found an increased lateralized ERP over the primary auditory cortex (T7/T8) about 130 ms after stimulus onset, with LRPs over the motor cortex (C1/C2) occurring later (about 270 ms after stimulus onset).…”
Section: Using Lrp As An Index Of Response Activationmentioning
confidence: 99%
“…We should note that although the auditory target stimuli in Experiment 1 were presented by the left or right speaker, the lateralized sensory activity elicited by the auditory stimuli should have a limited contribution to motor-related LRPs (e.g., Wascher, Schatz, Kuder, & Verleger, 2001; see also Dittrich, Kellen, &Stahl, 2014, andNeumann, van der Heijden, &Allport, 1986, for further discussion). For instance, Wascher et al (2001, Experiment 2) found an increased lateralized ERP over the primary auditory cortex (T7/T8) about 130 ms after stimulus onset, with LRPs over the motor cortex (C1/C2) occurring later (about 270 ms after stimulus onset).…”
Section: Using Lrp As An Index Of Response Activationmentioning
confidence: 99%
“…However, care should be taken if difference scores are used, since those have been shown to depend on the mean RT level (see, e.g., Dittrich, Kellen, & Stahl, 2014;Steinhauser & Hübner, 2008), which we found to be altered for the manual dynamic secondary task, but not for the dynamic secondary task with the nonword. One way to deal with such possible changes due to RT level differences across conditions might be to use proportional scores.…”
Section: Discussionmentioning
confidence: 86%
“…However, the delta plot slope depends on the exact nature of the task (cf. Proctor, Vu, & Nicoletti, 2003;Proctor & Shao, 2010;Dittrich, Kellen, & Stahl, 2014). The negative slope for the latter suggests that the Simon effect results from a conflict at the motor response stage, which decays over time.…”
Section: Delta Plots Of Stroop Datamentioning
confidence: 99%